Effects of doping on magnetic and transport properties of La₀.₈₅₋ₓSMₓAG₀.₁₅MnO₃‚La₀.₈₋ₓMₓAg₀.₂MnO₃ (M=Sm³⁺, Dy³⁺), (1x)La₀.₈Ag₀.₂MnO₃/xBiFeO₃ and Pr₀.₆Ca₀.₄₋ₓBaₓMnO₃ Manganites / Norazila Ibrahim - Ibrahim, Norazila (2014)
In this study, four manganites series with starting compositions La₀.₈₅₋ₓSMₓAG₀.₁₅ (x=0 -0 .2), La₀.₈₋ₓMₓAg₀.₂MnO₃ (M=Dy³⁺, Sm³⁺, x=0-0.15), (l-y) La₀.₈AG₀.₂MnO₃‚/yBiFe0₃ (y=0wt%-3.5wt%) and Pr₀.₆Ca₀.₄₋ₓBaₓMnO₃ (x=0-0.3) were prepared by solid-state reaction method in order to elucidate their physical properties. For La₀.₈₅₋ₓSMₓAG₀.₁₅MnO₃ (x=0-0.2) and La₀.₈₋ₓMₓAg₀.₂MnO₃ (M=Sm3+, Dy³⁺, x=0-0.15) series, the resistivity and magnetic measurements showed all samples exhibit transition from insulating to metallic behavior accompanying a paramagnetic to ferromagnetic transition as the temperatures was decreased. For x=0, two metal-insulator, MI transition peaks were observed at Tᴘ₁ and Tᴘ₂ in the resistivity curves. Both peaks and Curie temperature, Tc shifted to lower temperatures with increasing Dy³⁺ and Sm³⁺, indicating that the substitution weakened the double exchange process and enhanced the Jahn-Teller effect. The magnetoresistance peak was observed around Tᴘ₁ for all samples. The observed double peak behavior in the p(T) curve is suggested to be due magnetic inhomogeneity of the samples. Our result also showed that the inhomogeneity was strongly influenced by the lattice effect. For (l-v)La₀.₈Ag₀.₂MnO₃/yBiFe0 3 (y=Owt%-3.5wt%) composite series, the resistivity and susceptibility measurements showed both metal-insulator transition temperatures, Tᴍ₁ and paramagnetic-ferromagnetic transition temperature, Tc decreased with increasing BFO content indicating weakening of the double exchange, DE mechanism. The MR peak was observed around Tᴍ₁ for all samples which is ascribed to the intrinsic MR effect. Below the peak, the MR increased almost linearly with decreasing temperature for all samples and this ascribed to the phenomena of extrinsic MR. The highest MR% ( at 40 K) was observed for the x=1.5% sample which showed a MR of more than twice that of the undoped (x=0%) sample. This extrinsic effect is suggested to be related to improved spin polarize tunneling of conduction electrons between grains under external field as a result of improved spin alignment. It is suggested that BFO induced some kind of magnetoelectric coupling between BFO and LAMO leading to the enhancement of the process. For Pr₀.₆Ca₀.₄₋ₓABaₓMnO₃ (x=0-0.3) series, the electrical and magnetic measurements showed that the x=0 sample exhibit insulating behavior and an antiferromagnetic to paramagnetic transition behavior. On the other hand, Ba-doped samples exhibit transition from insulating to metallic behavior accompanying a paramagnetic to ferromagnetic transition as the temperatures were decreased. Both Tc and Tᴍ₁ of samples increase with increasing Ba concentration. Magnetoresistance, MR behavior indicates intrinsic MR mechanism for x=0.1 which changed to extrinsic MR for x> 0.2 as a result of Ba substitution. The weakening of charge ordering and inducement of ferromagnetic-metallic (FMM) state as well as increased in both Tc and Tᴍ₁ indicating enhancement of double exchange mechanism which is suggested to be related to the increase of tolerance factor, x and increase of eg₋electron bandwidth as <rᴀ> increase with Ba substitution.